2009
DOI: 10.1108/00070700910951470
|View full text |Cite
|
Sign up to set email alerts
|

Food tourism reviewed

Abstract: Purpose -The purpose of this paper is to review the contribution of food to tourism with particular reference to the importance of food tourism and the factors which are critical to its success, highlighting topics for future research. Design/methodology/approach -Findings are based on analysis of academic and practitioner materials in the public domain collected from a range of print and electronic sources. Findings -Food is the subject of various types of tourism product and is a common theme in marketing, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
380
1
67

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 488 publications
(456 citation statements)
references
References 31 publications
8
380
1
67
Order By: Relevance
“…To ensure that the main issues related to each research area were included, this study draws from systematic literature reviews in each field (e.g., Bazzani and Canavari [14], on alternative food networks and short food supply chains; Vuignier [15], on place marketing and place branding; Berg and Sevón [16], on food in place branding; and Henderson [17], for a review on food tourism). Based on these systematic literature reviews, the main elements that define each research stream have been identified, and relevant articles examining such topics have been retrieved from the reference lists.…”
Section: A Note On Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure that the main issues related to each research area were included, this study draws from systematic literature reviews in each field (e.g., Bazzani and Canavari [14], on alternative food networks and short food supply chains; Vuignier [15], on place marketing and place branding; Berg and Sevón [16], on food in place branding; and Henderson [17], for a review on food tourism). Based on these systematic literature reviews, the main elements that define each research stream have been identified, and relevant articles examining such topics have been retrieved from the reference lists.…”
Section: A Note On Methodsmentioning
confidence: 99%
“…Moreover, using local culture and produce may contribute to developing a "sense of place", making the destination more distinctive and attractive because local food and drinks allow places to capitalize on their assets to both benefit the local economy [60] and contribute to unique visitation experiences [41]. A unique sense of place is fostered by a clearly defined gastronomic identity and heritage, serving the differentiation and the rejuvenation processes alike [17].…”
Section: Local Resources and Actors For Place Branding Based On Fandgmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the second aspect, Henderson (2009) indicates that the retail and dining facilities (shops and restaurant/take-away facilities) at a destination are a core tourism product; consequently, food and drink outlets may be designed principally for tourists or depend heavily on them (as in the case of SANParks). Restaurants and takeaway facilities are generally assumed to be in the business of selling food only (Yüksel & Yüksel, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Eating is a form of tourist activity that gratifies all five senses (Chang et al, 2011;Kivela & Crotts, 2006;Loyd et al, 2011) and spending on food may constitute up to onethird of the total tourist expenditure (Boyne, Williams & Hall, 2002;Hall & Sharples, 2003;Telfer & Wall, 2000), thus comprising a significant proportion of tourism revenue (Mak, Lumbers & Eves, 2012). Food in an assortment of forms and enhancements is therefore an important tourist attraction and is central to the visitor experience (Ab Karim & Geng-Qing Chi, 2010;Henderson, 2009). The centrality of dining in the travel experience is manifested, not merely in its basic function as sustenance, but also in its various forms of benefits that augment the overall travel experience (Chang et al, 2011:307).…”
Section: Literature Reviewmentioning
confidence: 99%